A new species of semi-terrestrial freshwater crab (Crustacea: Decapoda: Brachyura: Potamidae) from the Central Highlands of Vietnam - Doweld, van Tu; Dang, van Dong; Cao, Thi Kim Thu; Hoang, Ngoc Khac (Zootaxa, 2016)
A new species of semi-terrestrial crab of the family Potamidae, Rathbunamon chumomrayense sp. nov. is described from Chu Mom Ray National Park, the Central Highlands of Vietnam. The new species can be distinguished from R. lacunifer (Rathbun, 1904), the only other species in the genus, by a suite of characters, including the slightly more rugose anterolateral regions, confluent epigastric and postorbital cristae that are sinuous, less convex anterolateral margins, relatively shorter fingers of the chelipeds, and the terminal segment of the male first gonopod being slightly curved outwards, with narrower dorsal flap.